(untitled) (DAPesquisa, 2025)
The celebration of femininity on social media, driven by women from younger generations, proposes a new narrative of acceptance of feminine characteristics, but, while resuming conservative standards regarding the feminine universe, it raises questions about its emancipatory and revolutionary character. This work proposes to discuss, through bibliographical research, the motivations behind this movement on the internet and evaluate the positive and negative impacts it has on society. Qualitative and descriptive research was applied. Qualitative Data Analysis was applied to interpret the results obtained. The results indicated a tendency among younger women who are very present on social media, especially on TikTok, to celebrate and resignify it, transforming it into a form of empowerment.